Performance leadership and management in elite sport: recommendations, advice and suggestions from national performance directors - Arnold, R.; Fletcher, C.; Molyneux, L. (European Sport Management Quarterly, 2012)
The purpose of this study was to elicit recommendations, advice and suggestions that can be used to enhance performance leadership and management in elite sport. To garner such information, 13 national performance directors were interviewed regarding the recommendations, advice and suggestions they had for leaders and managers of national sports teams and the sport organisations in which they operate. Five higher-order themes emerged for leaders and managers: establishing an approach, understanding roles within the team, developing contextual awareness, enhancing personal skills and strengthening relationships. There were also five higher-order themes for sport organisations: employing the most appropriate individual, creating the optimal environment, implementing systems and structures, developing an incluisive culture and providing appropriate support. As national governments place heightened importance on international sporting success, it is anticipated that the findings of this study will enable leaders, managers and sport organisations to more effectively address issues accompanying the leadership and management of Olympic programmes.